Efficacy and safety of olokizumab in the treatment of rheumatoid arthritis in real clinical practice in Kazakhstan - G. A. Togizbayev; D. I. Parpiyeva; D. A. Maksot (Современная ревматология, 2020)
Objective: Olokizumab (OKZ) is one of the innovative biologic treatments for rheumatoid arthritis (RA) targeting interleukin-6 (IL-6). The study purpose was to evaluate the 24-week efficacy and safety of OKZ in routine clinical practice among RA patients in Kazakhstan, filling a gap in existing research focusing on Western populations.Materials and methods: A 24-week, single-center, observational study. A total of 26 RA patients with moderate to high disease activity (by DAS28) despite methotrexate therapy received olokizumab 64 mg subcutaneously (every 4 weeks) combined with methotrexate. Disease activity (DAS28-CRP) was evaluated at baseline, at week 4, week 12 and at week 24.Results and discussion: 88% of patients were female, all were seropositive with median age of 53 years (range 24–73), and mean DAS28-CRP 5.5 ± 1.3. At week 24, a EULAR good and moderate response was observed in 19 (73.0%) patients. Significant improvements were noted from baseline DAS28-CRP by week 12 and week 24 (p<0.05). Remission rate (based on DAS28-CRP) was 50.0% (figure 2).  Olokizumab was generally well tolerated, with no unexpected safety findings.Conclusion: This real-world study confirmed efficacy and safety of olokizumab in line with previous RCT results in a predominantly Asian RA population, supporting its adoption in routine clinical management of RA as an effective and well-tolerated treatment option.